The Influence of Excipients on the Physicochemical and Biological Properties of a Bactericidal, Labile Ester Prodrug in a Salt Form – A Case Study of Cefetamet Pivoxil Hydrochloride - Dzitko, Jakub; Zalewski, Przemyslaw; Szymanowska, Daria; Garbacki, Piotr; Paczkowska, Magdalena; Piontek, Judyta Cielecka (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
The article presents an innovative approach to a bactericidal drug design based on a cephem prodrug analogue – cefetamet pivoxil hydrochloride. The emergence of cefetamet pivoxil hydrochloride excipient systems (mannitol, hydroxypropyl methyl cellulose, pregelatinised starch, lactose monohydrate, magnesium stearate, polyvinylpyrrolidone) caused changes in the physicochemical properties of cefetamet pivoxil hydrochloride. They are significant for planning the development of an innovative pharmaceutical formulation. The biological activity profile of the prodrug was also modified. FTIR spectra were used to study interactions between cefetamet pivoxil hydrochloride and the excipients. The theoretical approach to the analysis of experimental spectra enabled precise indication of cefetamet pivoxil hydrochloride domains responsible for interaction with the excipients. The interactions between cefetamet pivoxil hydrochloride and the excipients resulted in some important physicochemical modifications: acceptor fluid-dependent changes in solubility and the dissolving rate as well as a decrease in the chemical stability of cefetamet pivoxil hydrochloride in the solid state, especially during thermolysis. The interactions between cefetamet pivoxil hydrochloride and the excipients also had biologically essential effects. There were changes in its permeability through artificial biological membranes simulating the gastrointestinal tract, which depended on the pH value of the acceptor solution. Cefetamet pivoxil hydrochloride combined with the excipient systems exhibited greater bactericidal potential against Staphylococcus aureus. Its bactericidal potential against Enterococcus faecalis, Pseudomonas aeruginosa and Proteus mirabilis doubled. The new approach provides an opportunity to develop treatment of resistant bacterial infections. It will enable synergy between the excipient and the pharmacological potential of an active pharmaceutical substance with modified physicochemical properties induced by the drug carrier.